1967
DOI: 10.2136/sssaj1967.03615995003100040026x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Zinc Interactions in Flax

Abstract: Phosphorus‐Zn interactions in fiber flax, Linum usitatissimum L., were studied in growth chambers by means of a two‐zone root technique and nutrient solutions. Zinc and P were added separately from each other and the other essential elements; therefore, any interactions that occurred between them or with other elements had to take place at root surfaces or within the plant.Increasing either Zn or P in the substrate increased the concentration and total uptake of the respective element in the roots and tops of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Several experimental results indicate that inhibition of zinc translocation from roots to shoot and physiological inactivation of zinc within the shoots can occur (Boawn and Brown, 1968;Burleson and Page, 1967;Marschner, 1986). Phosphorus-zinc interactions in plants are well known.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental results indicate that inhibition of zinc translocation from roots to shoot and physiological inactivation of zinc within the shoots can occur (Boawn and Brown, 1968;Burleson and Page, 1967;Marschner, 1986). Phosphorus-zinc interactions in plants are well known.…”
Section: Resultsmentioning
confidence: 99%
“…Flax is a plant that is very susceptible to Zn deficiency, particularly at low soil temperatures (Moraghan 1980). This susceptibility is heightened by P application (Burleson and Page 1967;Jiao et al 2007;Loneragan et al 1979;Millikan et al 1968;Moraghan 1984;Spratt and Smid 1978) and also influenced by the presence of Fe, which determines normal chlorophyll formation and the development of green plant tissue (Lee et al 1969). Field studies have been conducted to evaluate the interactive effects of phosphate and ZnSC>4 fertilizers on different soil types and Cd uptake and their distribution in flax (Grant and Bailey 1997;Jiao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies, mostly on higher plants (e.g. Burleson & Page. 1967), have indicated that phosphate may antagonize the action of zinc.…”
Section: Introductionmentioning
confidence: 99%